Nanomechanical behavior of multi-walled carbon nanotubes particulate reinforced aluminum nanocomposites prepared by ball milling - Ostovan, Farhad; Matori, Khamirul Amin; Toozandehjani, Meysam; Oskoueian, Arshin; Mohamed Yusoff, Hamdan; Yunus, Robiah; Mohamed Ariff, Azmah Hanim (M D P I AG, 2016)
The nanomechanical properties of carbon nanotubes particulate-reinforced aluminum matrix nanocomposites (Al-CNTs) have been characterized using nanoindentation. Bulk nanocomposite specimens containing 2 wt % multiwalled CNTs (MWCNTs) were synthesized by a combination of ball milling and powder metallurgy route. It has been tried to understand the correlation between microstructural evolution particularly carbon nanotubes (CNTs) dispersion during milling and mechanical properties of Al-2 wt % nanocomposites. Maximum enhancement of +23% and +44% has been found in Young’s modulus and hardness respectively, owing to well homogenous dispersion of CNTs within the aluminum matrix at longer milling time.